Polycystic ovarian syndrome-current pharmacotherapy and clinical implications - Rumaisa Rashid; Suhail Ahmad Mir; Ozaifa Kareem; Tabassum Ali; Rifat Ara; Anjum Malik; Fiza Amin; G.N. Bader (Elsevier, 2022)
Polycystic ovary syndrome (PCOS), the most common endocrinopathy in women is characterized by polycystic ovaries, chronic anovulation and hyperandrogenism. The treatment in PCOS is mainly symptomatic and involves lifestyle interventions and medications such as Metformin, Oral contraceptives and Antiandrogens. However, the management of PCOS is challenging and current interventions are not able to deal with outcomes of this syndrome. This review encompasses latest pharmacotherapeutic and non-pharmacotherapeutic interventions currently in use to tackle various symptomatic contentions in PCOS. Our focus has been mainly on novel therapeutic modalities for treatment/management of PCOS, like use of newer insulin sensitizers viz., Inositols, Glucagon-like peptide-1(GLP-1) agonists, Dipeptidyl pepdidase-4 (DPP-4) inhibitors, and sodium-glucose transport protein 2 (SGLT2) inhibitors. Also, evidence suggesting the use of vitamin D, statins, and Letrozole as emerging therapies in PCOS have been summarized in this review. Additionally, novel cosmetic techniques like electrolysis, laser and use of topically applied eflornithine to tackle the most distressing feature of facial hirsutism associated with PCOS, non-pharmacological therapy like acupuncture and the role of herbal medicine in PCOS management have also been discussed.